2016
DOI: 10.4028/www.scientific.net/msf.869.935
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Microstructural Characterization of the Ti-25Ta-25Nb Alloy for Dental Applications

Abstract: Titanium and its alloys have been used in biomedical applications due to their excellent properties such as high corrosion resistance, biocompatibility and mechanical properties. In orthodontics, initially, it was common to use nickel-titanium alloys, however due to allergic reactions of patients, new titanium alloys containing elements such as niobium and tantalum are being studied. The Ti-25Ta-25Nb alloy is a β-titanium alloy and it has a low elastic modulus. In the present work, the ternary alloy was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Both conditions disclosed the β-phase and α"-metastable phase peaks. The β phase is a result of the Nb and Ta elements in the Ti-25Nb-25Ta system, which play a role as β stabilizers [42]. The α" is a metastable phase with an orthorhombic crystal system, corresponding a stage between the Hexagonal Closed Packed (hcp) and the Body Cubic Center (bcc) [43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…Both conditions disclosed the β-phase and α"-metastable phase peaks. The β phase is a result of the Nb and Ta elements in the Ti-25Nb-25Ta system, which play a role as β stabilizers [42]. The α" is a metastable phase with an orthorhombic crystal system, corresponding a stage between the Hexagonal Closed Packed (hcp) and the Body Cubic Center (bcc) [43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…The Ti-25Nb-25Ta alloy was previously studied by Seixas et al (2016) who identified the feasibility of its use in biomedical applications [14,17]. Recently, Silva et al (2023) verified the effects of adding 5%w of Sn, confirming better results for Ti-25Nb-25Ta-3Sn alloy.…”
Section: Graph Xrd1mentioning
confidence: 93%
“…The Ti-25Ta-25Nb-3Sn experimental alloy was obtained from sheets of titanium (grade 2), tantalum (99.99%), niobium (99.99%), and tin (99.99%). The methodology used in the processing was based on our previous studies with this alloy [14,17,18]. During melting, ingots were melted and re-melted at least ten times due to the difference between the melting point of these materials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations